The First Stereoselective Total Synthesis of the Immunosuppressive Decalin Derivative Monascusic Acid B - Kumar, Jayprakash Narayan; Das, Biswanath (Synlett, 2014)
The first stereoselective total synthesis of the immunosuppressive decalin derivative monascusic acid B has been accomplished from (R)-(+)-pulegone involving Horner–Wadsworth–Emmons and Julia–Kocienski olefination reactions and Lewis acid catalyzed intramolecular Diels–Alder cyclization.
Keywords: monascusic acid B; total synthesis; (R)-(+)-pulegone; Horner–Wadsworth–Emmons olefination; Julia–Kocienski olefination; intramolecular Diels–Alder cyclization; immunosuppressive effect